Dynamic (4D) CT perfusion offers simultaneous functional and anatomical insights into pulmonary embolism resolution. Issue 10 (October 2016) - Mirsadraee, Saeed; Reid, John H.; Connell, Martin; MacNee, William; Hirani, Nikhil; Murchison, John T.; van Beek, Edwin J.
Abstract: Objective: Resolution and long-term functional effects of pulmonary emboli are unpredictable. This study was carried out to assess persisting vascular bed perfusion abnormalities and resolution of arterial thrombus in patients with recent pulmonary embolism (PE). Methods and materials: 26 Patients were prospectively evaluated by dynamic (4D) contrast enhanced CT perfusion dynamic pulmonary CT perfusion. Intermittent volume imaging was performed every 1.5–1.7 s during breath-hold and perfusion values were calculated by maximum-slope technique. Thrombus load (modified Miller score; MMS) and ventricular diameter were determined. Perfusion maps were visually scored and correlated with residual endoluminal filling defects. Results: The mean initial thrombus load was 13.1 ± 4.6 MMS (3–16), and 1.2 ± 2.1 MMS (0–8) at follow up. From the 24 CTPs with diagnostic quality perfusion studies, normal perfusion was observed in 7 (29%), and mildly-severely abnormal in 17 (71%). In 15 patients with no residual thrombus on follow up CTPA, normal perfusion was observed in 6, and abnormal perfusion in 9. Perfusion was abnormal in all patients with residual thrombus on follow up CTPA. Pulmonary perfusion changes were classified as reduced (n = 4), delayed (systemic circulation pattern; n = 5), and absent (no-flow; n = 5). The right ventricle was dilated in 12/25 (48%) at presentation, and normal in all 26 follow up scans. Weak correlation was found between initial ventricular dilatation and perfusion abnormality at follow up (r = 0.15). Conclusions: Most patients had substantial perfusion abnormality at 3–6 months post PE. Abnormal perfusion patterns were frequently observed in patients and in regions with no corresponding evidence of residual thrombus on CTPA. Some defects exhibit delayed, presumed systemic, enhancement (which we have termed 'stunned' lung). CT perfusion provides combined anatomical and functional information about PE resolution.